PENGARUH OLAHRAGA TERHADAP TINGKAT HIPERTENSI PADA USIA LANJUT DI POSYANDU LANSIA DESA SEDATI KECAMATAN NGORO KABUPATEN MOJOKERTO - Seno, Seno; Sulis Diana; Dwi Helynarti Syurandhari (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Hypertension is also called "the silent killer" because it is often without complaints and the number of sufferers is most prevalent in old age. There are several factors that influence the occurrence of hypertension. The purpose of this study was to determine the effect of exercise behavior on the level of hypertension in the elderly at the Elderly Posyandu Sedati Village, Ngoro District, Mojokerto Regency. This study used a crossectional design with a population of elderly hypertension patients in Sedati Village, Ngoro Health Center Working Area, Mojokerto Regency as of October 2023 as many as 60 respondents within one month and a sample size of 52 respondents who met the inclusion criteria and were randomly selected. Data were collected by questionnaire and then analyzed using logistic regression. The results of the study explained that almost 50% of elderly respondents at Posyandu Lansia Sedati Village, Ngoro District, Mojokerto Regency never exercised. In addition, almost 50% of respondents at Posyandu Lansia Sedati Village, Ngoro District, Mojokerto Regency were diagnosed with pre-hypertension level of hypertension in old age and a small proportion had stage 2 hypertension. The results of logistic regression analysis show that there is an influence of exercise behavior (X2 = 8.919, p value = 0.000, Nagelkerke R Square = 0.754), stress (X2 = 8.473, p value = 0.000, Nagelkerke R Square = 0.768), and diet (X2 = 10.992, p value = 0.000 and Nagelkerke R Square = 0.730) on the level of hypertension in the elderly at the Posyandu Seniors Sedati Village Ngoro District Mojokerto Regency. Given the importance of exercise in reducing the level of hypertension, the elderly should actively participate in the elderly posyandu, take part in elderly gymnastics in order to have a better quality of life